Estrés laboral y el bienestar psicológico en los trabajadores de la empresa comercializadora ventas Corp. S.A. - Cedeño Triviño, Jennifer Guadalupe (2019)
Stress is defined as a physiological reaction of the organism to a situation that the person perceives as threatening; it is an automatic and necessary response to survival. When this natural response appears in excess, there is an overload of tension that affects the whole organism, and causes the appearance of diseases and alterations of health that impede the normal development and functioning of the human body. On the other hand, psychological well-being is a broad concept that includes social, subjective and psychological dimensions, as well as behaviors related to health in general that lead people to function in a positive way. It is related to how people struggle in their day to day facing the challenges they encounter in their lives, devising ways of managing them, learning from them and deepening their sense of meaning in life. The main objective of this research project is to establish the main consequences of work-related stress in the psychological well-being of the workers of the Comercializadora Ventas Corp. S.A. As a proposal the realization of coping techniques of work stress and psychological well-being in the workers of Comercializadora Ventas Corp. SA, will have as its scope to achieve greater awareness in the prevention of risks derived from work stress and in the application of techniques for anticipate and improve it.